2014
DOI: 10.1159/000355581
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Total Antioxidant Capacity in Saliva of Children with Severe Early Childhood Caries and Caries-Free Children

Abstract: Oxidative stress may play an important role in the onset and development of oral inflammatory and dental decay diseases. The aim of this study was to compare total antioxidant capacity (TAC) levels in the unstimulated whole saliva of children with severe early childhood caries (S-ECC) and caries-free children. In this case-control study, 80 children aged 3-5 years from nursery schools in Babol, northern Iran were the subjects of the study. The S-ECC group contained 40 children with dmfs ≥4 (age 3), ≥5 (age 4) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 12 publications
3
18
1
Order By: Relevance
“…In contrast to our results, other studies have shown significantly higher levels of TAC in dental caries [Tulunoglu et al, 2006;Hegde et al, 2009;Preethi et al, 2010;Dodwad et al, 2011;Kumar et al, 2011;Ahmadi-Motamayel et al, 2013;Mahjoub et al, 2014]. This difference might be attributed to the study population, sample size, the method of case selection or very high levels of oxidative stress, in which antioxidants cannot increase.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our results, other studies have shown significantly higher levels of TAC in dental caries [Tulunoglu et al, 2006;Hegde et al, 2009;Preethi et al, 2010;Dodwad et al, 2011;Kumar et al, 2011;Ahmadi-Motamayel et al, 2013;Mahjoub et al, 2014]. This difference might be attributed to the study population, sample size, the method of case selection or very high levels of oxidative stress, in which antioxidants cannot increase.…”
Section: Discussioncontrasting
confidence: 99%
“…There are also limited studies on salivary TAC in dental caries [Tulunoglu et al, 2006;Hegde et al, 2009;Preethi et al, 2010;Dodwad et al, 2011;Kumar et al, 2011;Mahjoub et al, 2014].…”
mentioning
confidence: 99%
“…; Mahjoub et al . ). In contrast, the total antioxidant capacity of saliva in periodontitis was lower than in healthy subjects (Diab et al .…”
Section: Introductionmentioning
confidence: 97%
“…In the oral cavity, the antioxidant defence system has been implicated with oral diseases where the level of antioxidant could be altered in response to an infection or disease. For example, a significant increase of antioxidant capacity in saliva was found in children with active and/or severe caries (Kumar et al 2011;Ahmadi et al 2013;Mahjoub et al 2014). In contrast, the total antioxidant capacity of saliva in periodontitis was lower than in healthy subjects (Diab et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a higher total antioxidant capacity (TAC) was observed with dental caries in deciduous but not in permanent teeth [17][18][19][20] and TAC increased with the age of the children [21,22].…”
Section: Open Accessmentioning
confidence: 99%